“Монгол хэлний гурван ном”-ын авианзүйн зарим онцлог - С.Батхишиг (Acta Mongolica, 2009)
In this paper, the author studies the peculiarities of phonetics and phonology in Mong-hak-sam-so and compared them to some characteristics of historical grammar of the Mongolian language. The Three Booksfor the Study ofMongolian written in Korean published in the late 18th century have become familiar in the sphere ofthe scientific field since the scholars and researchers have been studying it from the mid of 20th century. These books are considered to be rare monuments of Mongolian language phonology because Mongolian colloquial language ofthat time was recorded in both Mongolian script and Korean Hangeul script. Studying the language ofthe monument, we can see aspects ofBeijing Mongolian or Manchurian Mongolian speakers’ dialect ofthat period. During that period Mongolia was under the rule ofManchu so it is clear that Koreans who published these books based on the language of Mongolians who were influenced deeply by Manchu. In Mongolian Lao Ki-da, there are many occurrences of words with local dialects of Inner Mongolians such as biciba (mb. bicibe, kh. bichiv), kulya(mb. kuliy-e, kh. xuleey), bida(mb. bide, kh. bid) and kharchin and khorchin dialect words such as qoyalafkh. xoyula), qudaldu(mb.qudalduy-a, kh. xudalda) which originated as progressive assimilation ofphonemes became similar; examples of words with vowel assimilation which originated from rounded harmony of long vowels or phonemic conversion historical sound change like the modern ’u’ vowel replaced by ’o’ which occurs in such dialects as kharchin which are qalonfmb. qalayun > kh. xaluun), jaora(mb. jayur-a > kh. zuur). In The Three Booksfor the Study ofMongolian the fact that d phoneme is not written very few, it matches the disappearance of that phoneme in khorchin and kharchin dialect.